2017
DOI: 10.1038/srep40544
|View full text |Cite
|
Sign up to set email alerts
|

Sustained kidney biochemical derangement in treated experimental diabetes: a clue to metabolic memory

Abstract: The occurrence of biochemical alterations that last for a long period of time in diabetic individuals even after adequate handling of glycemia is an intriguing phenomenon named metabolic memory. In this study, we show that a kidney pathway is gradually altered during the course of diabetes and remains persistently changed after late glycemic control in streptozotocin-induced diabetic rats. This pathway comprises an early decline of uric acid clearance and pAMPK expression followed by fumarate accumulation, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Although the majority of epigenetic studies concern nuclear DNA modifications, mitoepigenetics also has an important role in a variety of diseases, including cardiovascular disease, obesity, and diabetes ( 99 ). For example, an increased methylation of D-loop region of mtDNA and subsequent reduction in the mtDNA copy number in leukocytes has been associated with insulin resistance in obesity ( 100 ), and decreased methylation of mtDNA has been linked with the reduced expression of PGC-1α and p-AMPK, and the accumulation of fumarate in diabetic kidney ( 101 ).…”
Section: Genetics Of Mitochondrial Dysfunction In Dnmentioning
confidence: 99%
“…Although the majority of epigenetic studies concern nuclear DNA modifications, mitoepigenetics also has an important role in a variety of diseases, including cardiovascular disease, obesity, and diabetes ( 99 ). For example, an increased methylation of D-loop region of mtDNA and subsequent reduction in the mtDNA copy number in leukocytes has been associated with insulin resistance in obesity ( 100 ), and decreased methylation of mtDNA has been linked with the reduced expression of PGC-1α and p-AMPK, and the accumulation of fumarate in diabetic kidney ( 101 ).…”
Section: Genetics Of Mitochondrial Dysfunction In Dnmentioning
confidence: 99%
“…Levels of TCA cycle intermediates including citrate, cis-aconitate, and fumarate have been reported to be elevated in diabetes and are correlated with albuminuria and kidney dysfunction in animal models of diabetes [43]. In addition, fumarate levels were increased in the kidney in STZ-induced diabetic rats [44]. In the present study, we found that no significant change of renal and urinary TCA cycle intermediates among all control mice (Figure 6c-f and Supplemental Figure 6, 7).…”
Section: Resultsmentioning
confidence: 99%
“…Sustained kidney biochemical alterations have been observed in these kidney cells even after tight glycemic control [10]. According to previous reports [11,12], there was a positive correlation between the structural and biochemical changes of the kidney tissue and the infrared (IR) absorption spectra.…”
Section: Introductionmentioning
confidence: 84%